The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.3758/bf03212251
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of psychometric functions from adaptive tracking procedures

Abstract: Because adaptive tracking procedures are designed to avoid stimulus levels far from a target threshold value, the psychometric function constructed from the trial-by-trial data in the track may be accurate near the target level but a poor reflection of performance at levels far removed from the target. A series of computer simulations was undertaken to assess the reliability and accuracy of psychometric functions generated from data collected in up-down adaptive tracking procedures. Estimates of psychometric f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
86
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 19 publications
9
86
1
Order By: Relevance
“…These results were obtained for either maximum-likelihood and probit analysis and they are in accordance with the study of McKee et al (1985). Similar results were found by Leek et al (1992) who compared the method of constant stimuli, APE, and UDTR.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These results were obtained for either maximum-likelihood and probit analysis and they are in accordance with the study of McKee et al (1985). Similar results were found by Leek et al (1992) who compared the method of constant stimuli, APE, and UDTR.…”
Section: Discussionsupporting
confidence: 84%
“…by Emerson (1986a), Kershaw (1985), Leek, Hanna and Marshall (1992), Lieberman and Pentland (1982), Madigan and Williams (1987), Maloney (1990), Rose, Teller and Rendleman (1970), Simpson (1989) or Swanson and Birch (1992). In this case, a model for the psychophysical observer is chosen and responses are generated according to the probabilities associated with this observer model.…”
Section: Discussionmentioning
confidence: 99%
“…Slope bias is larger for smaller step sizes (or, as Leek et al, 1992, put it, for a constant step size, slope bias increases with lower true slope of the PF). With constant step size, the amount of slope bias decreases with increasing run length.…”
Section: Discussionmentioning
confidence: 99%
“…The run lengths needed to get slope estimates with less than 10% error are rather high. Leek et al (1992) suggest runs of at least 200 trials. For shorter runs, they suggest correction factors.…”
Section: Discussionmentioning
confidence: 99%
“…By fitting a parametric model to the sequence of responses using a maximum likelihood criterion, it is possible to estimate both the SRT and slope at a chosen performance level. It has, however, been found that the slope estimates obtained in this way may have considerable bias (Leek et al, 1992;Kaernbach, 2001;Treutwein and Hansstrasburger, 1999). Wetherill (1963) derived expressions for the asymptotic variance of the maximum likelihood estimators ofã andb in Eq.…”
Section: B Methods For Estimating the Pfmentioning
confidence: 99%